Human Demodex Mite: The Versatile Mite of Dermatological Importance - Parvaiz Anwar Rather; Iffat Hassan (Wolters Kluwer Medknow Publications, 2014)
Demodex mite is an obligate human ecto-parasite found in or near the pilo-sebaceous units. Demodex folliculorum and Demodex brevis are two species typically found on humans. Demodex infestation usually remains asymptomatic and may have a pathogenic role only when present in high densities and also because of immune imbalance. All cutaneous diseases caused by Demodex mites are clubbed under the term demodicosis or demodicidosis, which can be an etiological factor of or resemble a variety of dermatoses. Therefore, a high index of clinical suspicion about the etiological role of Demodex in various dermatoses can help in early diagnosis and appropriate, timely, and cost effective management.